Breast and Axillary Lymph Node Metastases from Advanced Non-small Cell Lung Carcinoma - Jaudah A. Al-Maghrabi; Elshami M. Elamin; Hossam A. Abdel-Rahman (Journal of King Abdulaziz University: Medical Sciences, 2023)
Lung cancer metastasizing to the breast is rare. Only few published case reports can be found in the literature. Metastatic lung cancer to the breast and its ipsilateral axillary lymph node is extremely unusual. No awareness of any prior case reports of lung cancer with such a presentation is known. Herein, this study reports an unusual case of a middle aged Saudi female with non-small cell lung cancer that has metastasized, not only to the lungs and the breast, but also to the ipsilateral axillary lymph nodes. It is important for the oncologists to be mindful of rare presentations for such a common malignancy as lung cancer.